STUDENTS’ CONCEPTUAL UNDERSTANDING AND CHALLENGES IN LEARNING ENGLISH TENSES AT JUNIOR HIGH SCHOOLS - Syaharani Zahra Aisy Kuncoro; Fitriah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
English tenses play an important role in constructing accurate sentences and expressing clear ideas. Being able to use them accurately will help transfer the information effectively. This study aims to identify students' conceptual understanding of English grammar and the challenges they encounter in learning tenses by interviewing six students and administering grammar tests to 37 students. The results showed that students’ understanding of English tenses is limited to mastery of basic patterns and has not developed into contextual application. This finding was supported by the results of grammar tests indicating their understanding of sentence structure but they failed to distinguish verb forms and use them appropriately in sentences. This indicates that their understanding still focuses on memorizing the forms rather than applying them in real communication contexts. The study highlights the necessity of adopting more contextual and communicative approaches, such as practicing tenses in authentic situations like conversations and writing to enhance students' practical application skills.